Research Brings Nations Together (Raton, NM Raton Range, 1997)
The article is about the American and Russian scientist getting together to discuss and present technology being developed in a joint projects.
Newspaper article + Photographs 1)Pete Domenici 2) Joe Duncan
Master list item #: 71
File location is in the Raton file Cabinet
Keywords: Domenici, Pete -- U.S. Senator; Duncan, Joe -- Geophysicist; Stolarczyk, Larry -- Raton Technology Research President; Raton Technology Research Facilities; Losa Alamos National Laboratory; U.S. Industry Coalition Program; American Scientists; Russian Scientists; Technology Research Projects; Joint Projects; Landmind detector; Raton, New Mexico